Variação temporal em estrelas-do-mar Asterina stellifera (Echinodermata: Asteroidea) na Baía de Guanabara, Rio de Janeiro - Mascarenhas, Bernardo José de Araújo (1996)
Guanabara Bay, located in the State of Rio de Janeiro, is an area of multiple uses (e.g. ecology, tourism, fishing). The Bay has been through a process of environmental degradation, due to populational and industrial growth on its neighbourhoods. Morphometrical and numerical data on the seastar Asterina stellifera were collected during 1993 and 1994 at Guanabara bay for comparison with similar information collected in the early l980's. Besides, these parameters were compared throughout the year in the 1980' s inorder to detect variations. The quantity of specimens was compared by charts as was their size by means of statistical The results showed a reduction in the number of specimens and a increase in their body size between the two decades, as well as variations in quantity and size of specimens in different periods of the year in the l980's. Factors which may be related to the observed changes are discussed, and suggestions for further studies on the subject are given. Future researches on the populations of A. stellifera from Guanabara Bay, as well as environmental studies in the area, should benefit from this study.